Pesticide use by farmers in Puerto La Boca, Manabí. A reflection on its possible consequences - Julio Gabriel Ortega; Jonathan Ávila Demera; Fernando Ayón Villao; Jessica Morán Morán; Agustín Álvarez Plúa; Heidi Flores Ramírez (Journal of the Selva Andina Biosphere)
In order to reflect on the possible consequences of the use of pesticides by the farmers of Puerto La Boca, an investigation was implemented, a survey was prepared with 35 closed questions that were applied to 155 people (31 families). The experiment was implemented in a completely randomized experimental design in factorial arrangement with 2 factors, factor A: pesticide and/or organic products and factor B: Dosage. The results showed that the active ingredients for the most used liquid fungicides were Cymoxanil + Chlorothalonil, for the control of Oomycetes such as Pseudoperonospora cubensis, and Phytophthora infestans causing mildew in Cucurbitaceae and Solanaceae, respectively. Insecticides such as Imidacloprid and Methomyl were the most used to control aphids (Myzus persicae), green parrot (Empoasca sp.), leaf miner (Liriomyza trifolii), Thrips (Trips tabaci) and black lorikeets (Prodiplosis longifilia). The most used microorganisms were Trichoderma sp. and Bacillus thuringiensis, for the control of insect pests such as the moth (Diaphania sp.) and diseases such as Fusarium sp. And Rhizoctonia solani, in melon, watermelon, cucumber, onion, bell pepper and tomato crops. It was determined that farmers in Puerto La Boca under- and/or over-dosed solid and liquid fungicides and insecticides in their applications. Farmers need to strengthen their knowledge of pesticide use and management.